Dari Teks ke Konteks: Relevansi Metodologis Hermeneutik dalam Penafsiran Al-Qur’an dan Hadis Era Kontemporer - M. Nuzulul Ulum; Joko Kastiawan; Ma’ruf Nugroho (MAN 4 Kota Pekanbaru, 2026)
This study aims to analyze the relevance of the hermeneutic approach in interpreting the Qur'an and Hadith in the contemporary era by formulating a contextual interpretive framework. This research employs a qualitative approach through conceptual library research, examining classical and contemporary literature on hermeneutics in Islamic studies. The findings reveal that the hermeneutic approach operates through three main analytical dimensions: (1) reconstruction of the historical context of the text (historicity), (2) critical engagement of the reader’s socio-cultural context, and (3) a dialogical process between text, authorial intent, and present realities. These dimensions produce a contextual interpretive model that distinguishes between universal ethical principles (maqāṣid al-sharī‘ah) and context-bound legal formulations. Furthermore, the study identifies that the practical relevance of hermeneutics lies in its ability to reinterpret issues such as social justice, gender relations, and technological ethics within an Islamic framework without negating textual authority. Thus, hermeneutics does not replace classical exegesis but complements it by offering a systematic and adaptive methodological framework that enhances the responsiveness of Islamic teachings to contemporary challenges.